EFFECT OF SOYBEAN (Glycine max) AND LUPIN (Lupinusangustifolius) RATIOS STARTER TYPES, AND BOTH INTERACTIONS ON CHARACTERISTICS OF SUBSTITUTED TEMPEH - Hartantie, Kartini; Susilowati, Etty; Sutrisno, Asep Dedy; Sumartini, Sumartini (Jurnal Pertanian, 2020)
Indonesia’s high dependence on soybean imports as a raw material for tempeh has brought various efforts to find a substitute of this raw material. One of the most potential substitute is lupin (Lupinusangustifolius). However, the mass adoption of these beans as raw material for tempe production is still low. In this study, we test effects of several ratios between soybeans and lupine, by using mix starters on the characteristics and quality of a substituted tempeh. The results indicated that the best treatment for the substituted tempeh was a2b6 treatment with a 1: 2 ratio of soybeans and lupin by using the starter produced by Indonesian Institute of Sciences (LIPI). Moreover, the substituted tempeh has a low water and fiber content as well as sensory acceptable.